2022
DOI: 10.1038/s41598-022-05493-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of miR-145-5p and miR-146b-5p levels is linked to reduced parasite load in H9C2 Trypanosoma cruzi infected cardiomyoblasts

Abstract: In the heart tissue of acutely Trypanosoma cruzi-infected mice miR-145-5p and miR-146b-5p are, respectively, downregulated and upregulated. Here, we used the H9C2 rat cardiomyoblast cell line infected with the Colombian T. cruzi strain to investigate the parasite-host cell interplay, focusing on the regulation of miR-145-5p and miR-146b-5p expression. Next, we explored the effects of interventions with the trypanosomicidal drug Benznidazole (Bz) alone or combined with Pentoxifylline (PTX), a methylxanthine der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 103 publications
3
19
0
Order By: Relevance
“…Lastly, we validated miR-146b-5p in individual samples, based on differential expression found in the acute phase of T. cruzi infection [38], crucially shown in in vitro model of T.cruzicardiomyocyte interaction [76]. miR-146b-5p was found upregulated in acutely infected mice [38] and here in the vehicle-treated infected group, supporting the consistent effect of infection on miR-146b-5p expression in both acute and chronic phases of CD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Lastly, we validated miR-146b-5p in individual samples, based on differential expression found in the acute phase of T. cruzi infection [38], crucially shown in in vitro model of T.cruzicardiomyocyte interaction [76]. miR-146b-5p was found upregulated in acutely infected mice [38] and here in the vehicle-treated infected group, supporting the consistent effect of infection on miR-146b-5p expression in both acute and chronic phases of CD.…”
Section: Discussionsupporting
confidence: 63%
“…The effects of Bz+PTX therapy on CCC were also previously explored by our group, supporting reduction in myocarditis and fibrosis, improvement of ECG abnormalities, reduction of TNF, and TNFR1 expression on CD8 + T cells and, more importantly, these effects were sustained after 30 days of treatment suspension [26]. Additionally, we recently assessed miR-146b-5p expression in T. cruzi-infected H9C2 cardiac cells, showing upregulation of this miRNA in early hours of infection with expression restoration upon Bz+PTX therapy, corroborating the participation of this miRNA in the parasite-host interaction process [76].…”
Section: Discussionsupporting
confidence: 54%
“…Hadighi et al, (2022) have shown that assessment of miR-145 in the plasma level of Iranian Plasmodium vivax malaria patients can introduce a promising diagnostic biomarker [20]. Farani et al, (2022) have also shown that over-expression of miR-145-5p and miR-146b-5p is related to decreased parasite burden in Trypanosoma cruzi -infected cardiomyoblasts which can candidate as promising biomarkers of parasite control to apply treatment methods in Chagas disease [21]. As well, Mohammadi et al, (2021) have shown that microRNA-365 enhanced apoptosis in A375 human melanoma cells line treated with fertile HCF [5].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium vivax malaria patients can introduce a promising diagnostic biomarker [20]. Farani et al, (2022) have also shown that over-expression of miR-145-5p and miR-146b-5p is related to decreased parasite burden in Trypanosoma cruzi-infected cardiomyoblasts which can candidate as promising biomarkers of parasite control to apply treatment methods in Chagas disease [21].…”
Section: Hadighi Et Al (2022) Have Shown That Assessment Of Mir-145 I...mentioning
confidence: 99%
“…When the mimic/inhibitor systems were applied 48 h after infection, all systems except the miR-146b-5p inhibitor resulted in a reduction in parasite load. These findings suggest that miR-145-5p and miR-146b-5p may play a role in controlling signaling pathways crucial for interacting with the parasite and host cells [ 23 ]. Therefore, further investigation of these miRNAs is warranted as potential biomarkers for parasite control and tools to identify therapeutic adjuvants for etiological treatment in ChD.…”
Section: Methodsmentioning
confidence: 99%